Functional and semantic analysis of traditional and standardized units of measurement in English and Uzbek languages - Boboyeva , Muazzam Narimonovna (The Lingua Spectrum, 2026)
This article provides a comparative-typological analysis of the functional-semantic features of standardized and traditional units of measurement in English and Uzbek. The study examines the lexical-semantic structure of measurement units, their functional roles in speech, and their place in cultural-linguistic context. Semantic differences between traditional units (qarich, gaz, batman, misqol, etc.) and modern standardized units (meter, kilogram, liter, etc.) are identified and their significance from a linguistic perspective is demonstrated. The article also covers cognitive and pragmatic aspects of this lexical group.